Kultur Jaringan Kantong Semar (Nepenthes mirabilis) - Diny Dinarti; Urip Sayekti; Yayu Alitalia (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2010)
ABSTRACTThis research was about in vitro propagation of Pitcher Plant Nepenthes mirabilis. The aims of this research were to determine: 1) the influence of kind and concentration of in vitro medium and also plant growth regulator on germination of Nepenthes mirabilis, 2)the effect of BAP and NAA on shoot multiplication of N. mirabilis. This research consisted of three experiments and all experiments used Completely Randomized Design. On the first experiment MS (Murashige and Skoog) and KC (Knudson C) were used, i.e. full (1), three-fourth (3/4), one-half (1/2) and one-fourth (1/4) Salt Concentration. On the second experiment 10 composition media were used, i.e. ½ MS, ½ MS+TDZ 0.01 ppm, ½ MS+IAA 0.1 ppm, ½ MS+GA3 10 ppm, ½ MS+150 ml coconut water, 1/4KC, 1/4 KC+TDZ 0.01 ppm, ¼KC+IAA 0.1 ppm, 1/4KC+GA3 10 ppm and 1/4KC+ 150 ml coconut water. On the third experiment BAP with 0, 0.5, 1, 2 ppm and NAA 0, 0.1, 0.2, 0.5 ppm were used as factor for shoot multiplication.The result showed that KC medium was the best medium for germination percentage of N. mirabilis (64%). MS or KC medium with ½ or ¼ salt concentration was the suitable for germinating time of N. mirabilis (average 39 days after showing). Adding of TDZ, IAA, and GA3 significantly increased germination percentage (70 – 90%) and decreased germinating time (27 – 38 days after showing). Culture growth on medium with BAP 0 - 1 ppm was the best medium for shoot and leave induction. The best medium for root growth of N. mirabilis was MS or KC medium without NAA.Key words: Nepenthes mirabilis, MS, KC, TDZ, IAA, GA3, BAP, NAA, in vitro propagation, medium